WASATHIYAH AND THE ISLAMIC DA’WAH PROBLEMS IN INDONESIA - Ashari, Suhartini (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
At present, Muslims are required to be able to act with wasathiyah. Such a wasathiyah act shall be reflected from the ability to integrate two different dimensions, namely the hablun minAllah dimension and the hablun minan-nas dimension. This requirement is not the requirement of the era. It is the requirement of the Qur’an and the Hadith. The Wahhabi-Salafi da’wah promotes hardness. This paper is a library research by using a da’wah approach, especially in the study of people’s problems. A correct understanding of wasathiyah meaning will be able to establish a conscious attitude to perform a moderate Islam under a true meaning. In addition, this study also results in an understanding of da’wah attitudes in facing people attitudes, specifically any da’i who tends to ignore the guidance of wasathiyah and the ways of how to implement Islamic da'wah in order to realize wasathiyah